High-precision quasi-continuous atmospheric greenhouse gas measurements at Trainou tower (Orléans forest, France) - Schmidt, Martina; Lopez, M.; Yver Kwok, C.; Messager, C.; Ramonet, M.; Wastine, B.; Vuillemin, C.; Truong, F.; Gal, B.; Parmentier, E.; Cloué, O.; Ciais, P. (Atmospheric measurement techniques, 2014)
Abstract. Results from the Trainou tall tower measurement station installed in 2006 are presented for atmospheric measurements of CO2, CH4, N2O, SF6, CO, H2 mole fractions and radon-222 activity. Air is sampled from four sampling heights (180, 100, 50 and 5 m) of the Trainou 200 m television tower in the Orléans forest in France (47°57'53" N, 2°06'45" E, 131 m a.s.l.). The station is equipped with a custom-built CO2 analyser (CARIBOU), which is based on a commercial non-dispersive, infrared (NDIR) analyser (Licor 6252), and a coupled gas chromatography (GC) system equipped with an electron capture detector (ECD) and a flame ionization detector (FID) (HP6890N, Agilent) and a reduction gas detector (PP1, Peak Performer). Air intakes, pumping and air drying system are shared between the CARIBOU and the GC systems. The ultimately achieved short-term repeatability (1 sigma, over several days) for the GC system is 0.05 ppm for CO2, 1.4 ppb for CH4, 0.25 ppb for N2O, 0.08 ppb for SF6, 0.88 ppb for CO and 3.8 for H2. The repeatability of the CARIBOU CO2 analyser is 0.06 ppm. In addition to the in situ measurements, weekly flask sampling is performed, and flask air samples are analysed at the Laboratoire des Sciences du Climat et de l'Environnement (LSCE) central laboratory for the same species as well for stable isotopes of CO2. The comparison between in situ measurements and the flask sampling showed averaged differences of 0.08 ± 1.40 ppm for CO2, 0.7 ± 7.3 ppb for CH4, 0.6 ± 0.6 ppb for N2O, 0.01 ± 0.10 ppt for SF6, 1.5± 5.3 ppb for CO and 4.8± 6.9 ppb for H2 for the years 2008-2012. At Trainou station, the mean annual increase rates from 2007 to 2011 at the 180 m sampling height were 2.2 ppm yr-1 for CO2, 4 ppb yr-1 for CH4, 0.78 ppb yr-1 for N2O and 0.29 ppt yr-1 for SF6. For all species, the 180 m sampling level showed the smallest diurnal variation. Mean diurnal gradients between the 50 m and the 180 m sampling level reached up to 30 ppm CO2, 15 ppm CH4 or 0.5 ppb N2O during nighttime whereas the mean gradients are smaller than 0.5 ppm for CO2 and 1.5 ppb for CH4 during afternoon.